Efficacy of uterine flushing with human chorionic gonadotropin (hCG) on pregnancy rates in primary unexplained infertility: a randomized controlled trial - Parvin Hakimi; Mahshid Alborzi; Ehsan Nikkhou; Hosein Azizi (European Journal of Medical Research)
Abstract Background There are limited and controversial findings concerning ovulation induction using intrauterine and intramuscular human chorionic gonadotropin (hCG) injection compared to intramuscular hCG alone. The study aimed to examine the impact of intrauterine hCG injection, which is used to induce ovulation, on the efficacy of the intrauterine insemination (IUI) technique in patients with unexplained infertility. Methods A randomized controlled clinical trial was conducted involving 80 subjects with unexplained primary infertility at the infertility clinic of Al-Zahra Hospital in northwest Iran. Patients were randomly allocated into two groups: control and intervention. Both groups received initial treatment with letrozole and Recombinant follicle-stimulating hormone (r-FSH). After confirmation of at least one follicle measuring 18 mm or larger through ultrasonography, in the control group, two ampoules of 5000 units of hCG were administered intramuscularly. The intervention group received 500 units of hCG diluted in 0.5 cc of normal saline and was injected into the uterine cavity along with the two intramuscular ampoules. Primary outcomes were clinical and chemical pregnancy rates and the secondary outcome was any adverse pregnancy outcomes. Multiple logistic regression analysis was used to estimate crude and adjusted odds ratios (AORs) of the pregnancy rates with 95% confidence intervals (CIs). Results No significant differences were found between the two groups regarding baseline characteristics (p > 0.05). Chemical and clinical pregnancy rates in the control and intervention groups were (32.5 vs. 40%) (32.5% vs. 35%), respectively. In the final analysis after adjusting the potential confounders, intrauterine and intramuscular hCG injection increased the likelihood of chemical pregnancy by 1.39 times AOR = 1.42 (1.31–4.12; p = 0.036), and clinical pregnancy by AOR = 1.25 (1.03–3.74; p = 0.048) compared to intramuscular hCG alone. There were no statistical differences regarding adverse pregnancy outcomes between the study groups (p value > 0.05). Conclusions It seems that ovulation induction through intrauterine and intramuscular hCG injection increased the odds of both chemical and clinical pregnancy rates compared with intramuscular hCG alone. Multicenter clinical trials and meta-analysis studies are needed for decision making in clinical settings.